Economic planning under capitalism: The new deal and postwar France experiments - Fernando J. Cardim de Carvalho (Levy Economics Institute of Bard College, 2019)
By the beginning of the 20th century, the possibility and efficacy of economic planning was believed to have been proven by totalitarian experiments in Germany, the Soviet Union, and, to a lesser degree, Fascist Italy; however, the possibilities and limitations of planning in capitalist democracies was unclear. The challenge in the United States in the 1930s and in postwar France was to find ways to make planning work under capitalism and democratic conditions, where private agents were free to not accept its directives. This paper begins by examining the experience with planning during the first years of the New Deal in the United States, centered on the creation and operation of the National Recovery Administration (NRA) and the Agricultural Adjustment Administration (AAA), and continues with a discussion of the French experience with indicative planning in the aftermath of World War II. A digression follows, touching on the proximity between the matters treated in this paper and Keynes's view that macroeconomic stabilization could require a measure of socialization of investments, following James Tobin's hunch that French indicative planning, as well as some social democrat experiences in Northern Europe, could be playing precisely that role. The paper concludes by identifying the lessons one can draw from the two experiences.
Keywords: E02; E65; N12; N32; O21; 330; New Deal; National Recovery Act (NRA); National Industrial Recovery Act (NIRA); Economic Planning; Economic Cooperation